ANALISIS PENGARUH E-COMMERCE TERHADAP PERILAKU KONSUMTIF MAHASISWA (STUDI KASUS PADA MAHASISWA DI PRODI PENDIDIKAN AKUNTANSI UNIVERSITAS NEGERI MEDAN ) - sahlima hutagalung sahlima; Agustina Novita Silaban; Malika Auliya Putri; Jelita Maribet Gultom (Jurnal Riset Bisnis dan Ekonomi Digital, 2024)
This study aims to analyze the impact of e-commerce on the consumptive behavior of students in the Accounting Education program at Universitas Negeri Medan. With the rapid advancement of technology, e-commerce has become a primary choice for students when shopping. The research methodology employed a survey through questionnaires distributed to students to gather data on online shopping frequency, reasons for platform selection, and its impact on financial management. The results indicate that the majority of students actively engage in online shopping, driven by ease of access, product variety, and competitive pricing. However, high consumptive behavior has the potential to lead to poor financial management. This study suggests the importance of financial education to assist students in managing their expenses wisely. Thus, e-commerce can be utilized positively without significant negative consequences.